Effect of building designation on parking characteristics, road performance, and zoning regulation - da Costa, Don Gaspar Noesaku; Suni, Yulius P. K. (SINERGI, 2025)
If the capacity of the parking zone on buildings with great trip attractiveness rates is inadequate, it usually triggers on-street parking activity and its unintended derived impacts. Unfortunately, although this unintended situation may decrease traffic and road environmental quality, a similar situation always occurs. The initial field observation's result indicates that a change in building utilization may have influenced it. So, this study aims to assess the effect of parking accumulation rates due to a change in building utilization on the parking index and its impacts on road performance, including traffic accident risk. The existing parking index is influenced by parking accumulation and capacity, while the planning parking index is determined by comparing the parking accumulation and standardized parking space. In addition, the effect of on-street and road performance was assessed using results from similar previous studies. It was found that a change in building function significantly impacts the existing parking index value. It could not accommodate the increased trip rate, resulting in on-street parking activity. It influences a decrease in road capacity, travel speed, air pollutants, and sight distance (increasing accident risk level). This indicates that an institutional strengthening capability represented in an appropriate zoning regulation, which describes the type, number, and scale of activities allowed to be built in a particular corridor, is a compulsory requirement. Consequently, the ladder of urban land use planning should be re-reviewed. Implementing this new concept should be considered, especially in an urban fast-growth corridor.